Computational Assessment of Trace Elemental Composition in Andrographics paniculata and Aegle marmmelos Using EDXRF-Technique - Jyothsna , S.; Sammaiah, D. (Novel Aspects on Pharmaceutical Research Vol. 2, 2023)
The main aim of the present research work is to determine the trace elemental concentration in Andrographics paniculata (A. paniculata) and Aegle marmmelos (A. marmmelos) which are growing in Telangana using against various diseases by EDXRF Technique. X-ray fluorescence spectrometer is one of the most widely used and versatile technique was used to study the trace element analysis. In this present work we measured thirteen elements and determine their elemental composition presence in selected medicinal plant samples of A. paniculata and A. marmmelos (by using EDXRF technique). From this it should be noted that, the variation in elemental composition of same plants from different regions, which can be compared with Standard certified values of NIST 1515 apple leaf given a good agreement. The variation in elemental composition can be changing of climate conditions and various mechanisms of plants. It is hoped that our elemental composition data of these medicinal plants available in Telangana region is very useful to pharmaceutical labs for invention of new drugs used for curing various diseases.